IMPLEMENTASI KESELAMATAN DAN KESEHATAN KERJA PADA PEKERJAAN PEMELIHARAAN RUTIN JALAN NASIONAL BLANGKEJEREN – LAWEAUNAN SECARA SWAKELOLA - Muhammad - Iqbal; Muhammad Isya; Hafnidar A.Rani (Prodi Magister Teknik Sipil Unsyiah, 2018)
Routine maintenance on the Blangkejeren - Laweaunan road is done by self-managed and continuously every year with road length 65 Km. The committing officer undertakes work with the subcontractor who is deemed capable of carrying out the work and provides wages to the foreman who is a resident. To avoid risks, the Committing Officer undertakes the implementation of the Occupational Safety and Health Management System (OSHMS). Therefore, this study aims to identify the level of OSH risk in routine road maintenance work, identify the level of compliance of subcontractors and workforce employees in OSH implementation on routine maintenance work, and identify the selection of service providers in each routine road maintenance work. The identification of OSH risk level is made based on the Minister of Public Works Regulation no. 05/PRT/M/2014 criteria, and data collected by interviewing the owner's personal. Identification of labor compliance rates of subcontractors and foremen is based on Construction and Building Guidelines No. 004/BM/2006, judged from the use of Personal Protective Equipment (PPE). The analysis method used in this study is descriptive analysis. The result from the analysis indicates that the level of OSH risk in routine national road maintenance work for the routine maintenance of pavement, routine road shoulder maintenance, and routine maintenance of road equipment has a low risk. Whereas in routine maintenance work of sewer, drainage, trenching and heap have a medium risk. Labor compliance from subcontractors has shown a higher percentage about 59% compared to 40% for labor compliance from the foreman. It means that most of the subcontracted workforce is compliant, and almost half the workforce of the foremen adheres to the use of PPE. The routine maintenance work of sewer, drainage, trenching and heap, the right service.